Scienza, Matematica e Regime - Guerraggio, Angelo (Chimica nella Scuola, 2022)
Without Fascism, would Italian science have developed along the same trajectories and at the same rhythm? More specifically: have the regime and its main exponents shown any particular attention to research and its applications with the aim of shaping a “Fascist science”? And how did the men of science react to such a somewhat cumbersome political presence and to the repressive attitudes of Fascism when it targeted universities and research? What were the consequences of those twenty years for the development of Italian science in the second half of the century? Some answers to these questions are provided by focusing on Mathematics, traditionally considered the most impermeable science to the social and political context, and which was very developed in Italy, even at the end of the First World War.